A Monoclonal Antibody that Does Not Recognize Tissue-Type Plasminogen Activator Bound to Its Naturally Occurring Inhibitor - Schleef, Raymond R; Wagner, Nancy V; Sinha, Manjula; Loskutoff, David J (Thrombosis and Haemostasis, 1986)
Hybridoma clones specific for tissue-type plasminogen activator (tPA) were screened in solid-phase radioimmunoassays for their reactivity toward free tPA and tPA complexed to the endothelial cell-derived, (3-migrating plasminogen activator inhibitor (β-PAI). Two monoclonal antibodies (MABs) were identified with quite distinct properties. The first, MAB LI72D1, bound to free tPA but did not recognize tPA complexed to the β-PAI, whereas the second, MAB HI72C1, bound both to free tPA and to tPA in complex with β-PAI. These properties were maintained when the MABs were immobilized to plastic micro- titer wells, thus permitting the development of immunoradiometric assays (IRMAs) to quantitate free tPA and total tPA antigen in various samples. The IRMAs were employed to analyze the tPA in media conditioned by several human cell types. The results indicate that in some cases, tPA may be present entirely as a free and active enzyme, while in others it apparently exists entirely in complex with β-PAI. Interestingly, some cells appear to contain both forms of tPA.
Keywords: Plasminogen activator; Inhibitor; Immunoradiometric assay; Monoclonal antibody; Immobilized enzyme